A ambientalização curricular da educação física nos contextos da pesquisa acadêmica e do ensino superior - Rodrigues, Cae (2013)
The aim of this research revolves around the following question: considering the global dimension of the environmental happening and the consequent tendency towards the environmentalization of curricula, how do these processes evolve in physical education settings, especially in contexts of research and teaching? For the analysis of environmentalization processes surrounding research contexts in physical education settings we considered papers published in scientific journals that propose dialogues/investigations revealing possible meeting points between environmental and physical education discourses. For the analysis of environmentalization processes surrounding teaching contexts in physical education settings we considered academic units that support discussions concerning environmental issues and that are part of physical education curricula in Brazilian higher education settings. The data was analyzed in dialogue with the theoretical references of the research. These references address, in the main: (a) the characterization of the socioenvironmental issue as a field of disputes of power and the elements that surround the legitimization and institutionalization of the environmental dimension; (b) curriculum theories and processes of curricular environmentalization in higher education settings; (c) the historical contextualization of meeting points between the field of physical education and the environmental field. Interpretative analysis of the data and the sociological focus of the research allow the identification of grounding symbols and structures of knowledge that are associated with the incorporation of environmental issues in physical education settings, especially in the contexts of research and teaching.